2013
DOI: 10.1111/jpc.12470
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective review of 200 children hospitalised with acute asthma. Identification of intervention points: A single centre study

Abstract: Unlike other common respiratory diseases requiring hospitalisation, biological factors are unlikely major contributors to the known gap in asthma outcomes between Indigenous and non-Indigenous children. Intervention points include better identification, documentation and management of tobacco smoke exposure, delivery of salbutamol and discharge planning (including education and utilisation of asthma action plans).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2014
2014
2109
2109

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…Students in our study reported high exposure to tobacco smoke at home (63%), far exceeding nationally reported data (7.8%) ( 2 ). This is consistent with our previous study on children hospitalized for asthma, which reported high exposure to tobacco smoke at home (Indigenous 95.2% and non-Indigenous 45.7%) ( 35 ). Our results highlight the importance of integrating interventions during adolescence to target social norms, behaviors, and attitudes ( 36 ) to prevent the uptake of tobacco smoking and prevent poorer long-term outcomes [e.g., chronic respiratory diseases such as bronchiectasis ( 35 ) and cardiovascular disease] ( 37 ).…”
Section: Discussionsupporting
confidence: 93%
“…Students in our study reported high exposure to tobacco smoke at home (63%), far exceeding nationally reported data (7.8%) ( 2 ). This is consistent with our previous study on children hospitalized for asthma, which reported high exposure to tobacco smoke at home (Indigenous 95.2% and non-Indigenous 45.7%) ( 35 ). Our results highlight the importance of integrating interventions during adolescence to target social norms, behaviors, and attitudes ( 36 ) to prevent the uptake of tobacco smoking and prevent poorer long-term outcomes [e.g., chronic respiratory diseases such as bronchiectasis ( 35 ) and cardiovascular disease] ( 37 ).…”
Section: Discussionsupporting
confidence: 93%
“…5,10,11 For example, the hospitalization and mortality rate for asthma is 2-3 times higher in indigenous Australians. 12 The poorer clinical outcomes have also been documented in indigenous children of New Zealand, Canada and USA as well as other minority groups globally. 5,13 There is little data on whether the risk factors for having asthma in indigenous children are identical to that in non-indigenous children.…”
Section: Asthmamentioning
confidence: 99%
“…5 An Australian study of 200 children hospitalized for asthma found that intrinsic biological factors are unlikely to account for the poorer asthma outcomes as there was no significant difference between indigenous and non-Indigenous children in the length of hospitalisation and risk factors (eg prematurity), other than environmental tobacco smoke (ETS) exposure. 12 The retrospective Australian study also identified possible intervention points to improve the management of asthma, particularly in indigenous children. These included better identification, documentation and management of ETS exposure, and improvement of acute management and discharge planning including education and utilisation of asthma action plans.…”
Section: Asthmamentioning
confidence: 99%
See 1 more Smart Citation
“…Distinctive challenges related to geographic barriers contribute to the uncertainty experience for native Hawaiian parents living on rural islands. Aboriginal peoples (First Nations, Inuit, and Métis) of Canada (Watson et al, 2012), indigenous New Zealand Māori (Jones, Ingham, Cram, Dean, & Davies, 2013), and Aborginal and Torres Strait Islander people of Australia (Giarola et al, 2014) live in remote areas and encounter similar geographic barriers to hospitals and spirometry testing (Castleden et al, 2016), social and health services (Ely & Gorman, 2010), specialty medical services (Chang et al, 2000), and asthma education and support (Watson et al, 2012).…”
Section: Discussionmentioning
confidence: 99%